Differential Transform Method for Solving Volterra q-Integral Equations (Contemporary Mathematics, 2023)
In this paper, Volterra q-integral equations are solved by using the method of q-differential transformation. Exact solutions of linear and nonlinear q-integral equations have been investigated. To illustrate the method, several problems are discussed for the effectiveness and performance of the proposed method.
Keywords: q-differential transform method; Volterra q-integral equations; integral transforms; q-calculus